Strategies for Managing Employees during Mergers and Acquisitions - Asdar, Muhammad (Advances in Human Resource Management Research, 2023)
Purpose: This study investigates strategies for effective employee management during mergers and acquisitions (M&A), aiming to identify approaches that mitigate negative impacts on staff and ensure successful organizational integration. Research Design and Methodology: Employing a qualitative research design, the study systematically reviews and synthesizes literature on employee management in M&A contexts. Key themes are extracted through thematic analysis of scholarly articles, books, and reports, providing a comprehensive view of human resource challenges during M&A. Findings and Discussion: Results emphasize the importance of effective communication, strong leadership, and active employee involvement. Transparent communication is crucial for reducing uncertainty and building trust, while transformational leadership guides employees through transitions, bolstering resilience and commitment. Employee participation in the integration process fosters ownership and aids in merging organizational cultures, enhancing morale and productivity essential for M&A success. Implications: The findings advocate for a holistic approach to employee management in M&A, integrating communication, leadership, and participation. Practically, it suggests creating an inclusive environment to facilitate transitions and achieve synergies. Theoretically, it enriches the dialogue on organizational change and human resource management, offering insights for future research on M&A dynamics.